The Relationship of Hip Fracture and Proximal Femur Geometry - Ulusoy, H.; Bilgici, A.; Kuru, O.; Saryca, N.; Arslan, S.; Erkorkmaz, U. (Elsevier Science Inc, 2007)
…
17th Scientific Meeting of the International-Bone-and-Mineral-Society -- JUN 24-29, 2007 -- Montreal, CANADA